Correlation of Abnormal Uterine Bleeding (AUB) with Thyroid Profile and Endometrial Biopsy - Koirala, Shraddha; Pande, Kricha; Shrestha, Sama (Nepal Medical College Journal, 2021)
Abnormal uterine bleeding (AUB) is defined as any change in the frequency of menstruation, duration of flow or amount of loss. Menstrual disturbances and different endometrial pattern may accompany and precede thyroid dysfunction. The objective of the study was to correlate thyroid profile with endometrial biopsy in cases of AUB. This study was conducted on 74 patients who presented with AUB, had undergone TFT and endometrial biopsy/hysterectomy. Among 74 patients, thyroid disorders were identified in 26 patients. Maximum number of patients with AUB belonged to the category of hypothyroidism (27%) and 8.1% of cases had hyperthyroidism. In the present study 29 (39.1%) had proliferative endometrium, followed by secretory pattern in 21 (28.4%) patients. Hormone induced changes was seen in 3 (4.1%) patients. Disordered proliferative endometrium and endometrial hyperplasia was observed in 6 patients (8.1%) each. Malignant lesion was not common and it comprised of only 1.4% cases. AUB is frequently seen in patients with thyroid dysfunction. Thyroid function test is a cost effective, easily available test and can detect a possibly curable cause of AUB and avoid unnecessary intervention like hormonal treatment and hysterectomy. AUB due to endometrial cause is an age related pathology. Histopathological examination of endometrial biopsy is a major diagnostic tool in evaluation of AUB. It helps the physician to plan therapy for successful management of AUB.